Evaluation of cytotoxicity, loading, and release activity of paclitaxel loaded-porphyrin based metal-organic framework (PCN-600). Issue 1 (January 2023) - Hamidian, Khadijeh; Barani, Mahmood; Adeli-Sardou, Mahboubeh; Sarani, Mina; Daliran, Saba; Oveisi, Ali Raza
Abstract: Considering the inducement side impacts and precipitation of continual doses in conventional therapeutic treatments, there is an urgent need in the field of drug delivery for novel designs of biocompatible carriers with wide loading dimensions and particularly the ability to control their drug release. In this work, we succeeded in synthesizing an iron-based organic metal framework based on iron-porphyrin (PCN-600) through a solvothermal method to function as a drug delivery system (DDS). According to SEM results, PCN-600 crystals a hexagonal-rod shaped morphology with the length of 300 nm and width of 100–300 nm. As an anticancer drug, Paclitaxel (PTX) was successfully loaded into the porphyrin-based metal-organic framework (PCN-600) via in-situ encapsulation; the loading efficiency was measured to be about 87.3%. In addition, PTX-encapsulated PCN-600 displayed a controlled and sustained release for up to 24 h of release assessment at the physiological microenvironment of pH = 7.4. Abstract : PCN-600; Drug delivery; Paclitaxel; Anticancer drugs; Metal-organic frameworks.